Preparation of Monodispersed Cs0.33WO3 Nanocrystals by Mist Chemical Vapor Deposition for Near-Infrared Shielding Application - Lei Huang; Hua Tang; Youjun Bai; Yong Pu; Lu Li; Jiang Cheng (Nanomaterials, 2020)
In this study, single-phase Cs0.33WO3 nanocrystals were synthesized by a novel mist chemical vapor deposition method. As prepared, Cs0.33WO3 nanocrystals exhibited a microsphere-like appearance constructed with angular crystal grains with an average size of about 30–40 nm. Characterization by X-ray photoelectron spectroscopy indicated that Cs0.33WO3 nanocrystals consisted of mixed chemical valence states of tungsten ions W6+ and W5+, inducing many free electrons, which could scatter and absorb near-infrared (NIR) photons by plasmon resonance. These Cs0.33WO3 microspheres consisted of a loose structure that could be crushed to nanoscale particles and was easily applied for producing long-term stable ink after milling. Herein, a Cs0.33WO3/polymer composite was successfully fabricated via the ultrasonic spray coating method using mixed Cs0.33WO3 ink and polyurethane acrylate solution. The composite coatings exhibited excellent IR shielding properties. Remarkably, only 0.9 mg cm−2 Cs0.33WO3 could shield more than 70% of NIR, while still maintaining the visible light transmittance higher than 75%. Actual measurement results indicate that it has really good heat insulation properties and shows good prospect in heat insulation window applications.